2013
DOI: 10.4236/ojg.2013.32b011
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectrical Survey for Engineering Investigation

Abstract: Water seepage erosion has been and remains one of the major engineering problems. However, most engineers will much depend on borehole data and soil test for designing and problem detection. By considering of the cost and destructive method, selection of geoelectrical prospecting would be appropriate. Therefore, two electrical geophysical surveys were carried out in Sekolah Menengah Kebangsaan Dato' Haji Mohd Nor, Gelugor, Pulau Pinang to map the presence of the unknown underground water sources (saturated zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…For both SP and Magnetic surveys were interpreted, the half width rules was used with the distance along the x-axis and SP data and magnetic residual data on the y-axis using excel graph to determined the aquifer depth as shown in Figure 2-5 and the result of half width rules which was obtained from the graph was also shown in Table 1; the mean value, standard deviation, Pearson's correlation coefficient, Testing the significance of r (2-tailed) and Correlation significant at 0.8 which is a strong correlation is shown in Table 2 obtained from Equation (1 & 2). Self-Potential: A total of 84 points were carried out, the field data obtained was interpreted using surfer 8 software, the survey coordinates and SP measurement were input into the software and the results were displayed in contoured map which obtained from non-polarizing coppercopper sulfate electrodes are very related to seepage flow patterns and the anomalies were positive and negative in this study which ranges from -30mV to +35mV as shown in Figure 6, inflow fluid produces negative potentials, the fluid outflow results produces positive potentials, which is in agreement with Mizunaga et al (2006), Leonard et al (2011), Teh-Saufia et al (2013.…”
Section: =supporting
confidence: 73%
See 2 more Smart Citations
“…For both SP and Magnetic surveys were interpreted, the half width rules was used with the distance along the x-axis and SP data and magnetic residual data on the y-axis using excel graph to determined the aquifer depth as shown in Figure 2-5 and the result of half width rules which was obtained from the graph was also shown in Table 1; the mean value, standard deviation, Pearson's correlation coefficient, Testing the significance of r (2-tailed) and Correlation significant at 0.8 which is a strong correlation is shown in Table 2 obtained from Equation (1 & 2). Self-Potential: A total of 84 points were carried out, the field data obtained was interpreted using surfer 8 software, the survey coordinates and SP measurement were input into the software and the results were displayed in contoured map which obtained from non-polarizing coppercopper sulfate electrodes are very related to seepage flow patterns and the anomalies were positive and negative in this study which ranges from -30mV to +35mV as shown in Figure 6, inflow fluid produces negative potentials, the fluid outflow results produces positive potentials, which is in agreement with Mizunaga et al (2006), Leonard et al (2011), Teh-Saufia et al (2013.…”
Section: =supporting
confidence: 73%
“…A resultant magnetic field is created which encompasses the earth and can be represented as a vector quantity having a unique magnitude and direction at every point on the earth's surface. The earth's magnetic field is not completely stable says by Teh-Saufia et al (2013). Both naturally-occurring and man-made magnetic materials can locally modify the earth's magnetic field as reported by EPA (2016).…”
Section: Basic Concept Of Ground Magnetic Methodsmentioning
confidence: 98%
See 1 more Smart Citation